Respuesta :

2a-4 is the answer you’re looking for

Answer:0

Step-by-step explanation: Calculation:

(

a

2

)

2

=

0

a

2

4

a

+

4

=

0

p

=

1

;

q

=

4

;

r

=

4

D

=

q

2

4

p

r

=

4

2

4

1

4

=

0

D

=

0

a

1

,

2

=

q

±

D

2

p

=

4

±

0

2

=

2

±

0

a

1

,

2

=

2

±

0

a

1

=

a

2

=

2

Factored form of the equation:

(

a

2

)

(

a

2

)

=

0

(a−2)

2

=0

a

2

−4a+4=0

p=1;q=−4;r=4

D=q

2

−4pr=4

2

−4⋅1⋅4=0

D=0

a

1,2

=

2p

−q±

D

=

2

0

=2±

0

a

1,2

=2±0

a

1

=a

2

=2

Factored form of the equation:

(a−2)(a−2)=0

ACCESS MORE